Effects of stretching exercises for posture correction: systematic review - Filho, José Nunes Da Silva; Gurgel, Jonas Lírio; Porto, Flávia (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: Nowadays, postural problems are widely discussed concerns because they involve quality of life and interfere with the functional aspects of individuals. Thus, muscle stretching exercise is suggested as useful in treating postural deviations. Objective: To investigate the effect of muscle stretching on body posture and analyze aspects of prescription and evaluation methods in order to relate the proposed training and results. Method: This systematic review was previously registered and accepted in International Registry Of Systematic Reviews (PROSPERO, id: CRD42013005280), and described according to the recommendations of the PRISMA. The search data began with the choice of key terms and their synonyms, according to the Descritores em Saúde (DeCS) and MeSH. After, seeking material was performed on the major databases of scientific information (SciELO; PEDro, PubMed and Google Scholar). The studies that met the eligibility criteria underwent an evaluation as to their methodological quality based on the Brazilian - Portuguese version of the PEDro scale. Results: It was found seven clinical trials, methodologically scored, following Pedro scale, which showed little evidence about the topic, which contain significant limitations and/or low methodological quality. Conclusion: There are few evidence on the effectiveness of the intervention with exercise stretching in correcting postural deviations, making it difficult to reach consensus or conclusions.